iMASON : towards influence-driven multi-level analysis of online social networks - Li, Hui (2012)
Social network is a social structure of nodes that are tied by various kinds of relationships, such as kinships, friends, web links, colleagues, citation links, etc. Recently, large on-line social networks have become very popular among web users. A key feature of many online social networks is that they are driven by social influence between users. Specifically, the structural and semantic properties of individuals, communities and network can be traced back to the social influence effect. Hence, studying the social influence between users in a network is of great importance in many applications such as viral marketing, online advertising, advanced web architecture design, etc.